Evaluación de la posición natural de la cabeza y su relación con las maloclusiones dentales en la población de 6 a 18 años de edad en el municipio de Buenavista- Quindío (2023)
Association of head and cervical posture with malocclusion has been studied for many years and despite the encouraging research, no conclusive evidence has been reached for clinical application. There are no studies reported in Quindío, that associate malocclusion with head position or other facial variables, therefore, this research aimed to evaluate the correlation of natural head position with dental malocclusions in the population aged 6 to 18 years in the municipality of Buenavista-Quindío. 219 school children were included who underwent clinical and photographic analysis to establish sociodemographic and clinical data, Angle malocclusion classification, head posture and facial analysis, which were analyzed by contingency tables and chi-square. It was found that Class II was the most common malocclusion (36.5%), Class I ranked second (35.6%), and finally, Class III is the least common of the three types of malocclusion, with a percentage of 27.9%, and only a statistically significant association (P=0.045) was found between Class II malocclusion and overweight according to body mass index, in children with mixed dentition. In conclusion, for the school population of Buenavista, Quindío, there is no association between malocclusion and head position or facial variables.